The Effect of Educational Media on the Knowledge and Attitude of Personal Hygiene in Food Handlers - Wulandari, Okta Viani Wulandari; Kurniasari, Ratih (Universitas Muhammadiyah Surakarta, 2025)
Pendahuluan: Personal hygiene pada penjamah makanan adalah kegiatan menjaga kebersihan diri dan lingkungan kerja untuk mencegah kontaminasi makanan dan memastikan kesehatan konsumen. Penelitian ini bertujuan untuk mengetahui pengaruh media edukasi terhadap perubahan pengetahuan dan sikap penjamah makanan tentang personal hygiene di restoran SMKN 2 Karawang. Metode: Penelitian ini menggunakan pendekatan quasi eksperimen dengan desain one group pre-post test menggunakan Teknik total sampling dengan jumlah sampel sebanyak 30 responden. Uji Wilcoxon signed rank test digunakan untuk analisis statistik. Hasil: Diperoleh hasil yang signifikan antara pengetahuan dan sikap dengan media leaflet, media music video dan media game dengan p-value <0,05. Simpulan: Terdapat pengaruh media leaflet, media music video, media game terhadap pengetahuan dan sikap penjamah makanan di restoran SMKN 2 Karawang. Introduction: Personal hygiene of food handlers is a crucial issue in the food industry, as inadequate hygiene practices can increase the risk of food contamination, impact consumer health, and threaten food safety standards. This study aims to determine the effect of leaflet media, music video media and game media on changes in knowledge and attitudes of food handlers about personal hygiene at SMKN 2 Karawang restaurant. Method: This research uses a quasi-experimental approach with a one group pre-post test design using total sampling technique with a sample size of 30 respondents. Three educational media used as a reference for group division with 30 respondents as samples, so that 3 groups were made, namely the leaflet media group, the music video media group, and the game group, with 10 respondents belonging to each group. The Wilcoxon signed rank test was used for statistical analysis. Results: Obtained significant results between knowledge and attitudes with leaflet media, music video media and game media with a p-value <0,05. The highest average value for knowledge after being given education using the three media was the same (11.90 ± 0.316), while the highest average value for attitude after being given education was using leaflet and game media (9.80 ± 0.422). Conclusion: There is an effect of leaflet media, music video media, game media on the knowledge and attitude of food handlers in SMKN 2 Karawang restaurant.